Pemanfaatan Vegetasi Mangrove sebagai Obat-obatan Tradisional pada Lima Suku di Papua - -, Mahmud; -, Wahyudi (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2014)
AbstractMangrove plays important role to coastal communities across Papua. Mangrove provides food, material construction, firewood, medicine, shelter and others. This research is designed to determine the traditional practices of utilizing mangrove vegetation used for medicinal material remedieson for five ethnicgroups in Papua. Field observation, and intensive literature reviews were used to collect the data and information required. The results showed that seven spesies of mangrove belonging to five families were used for medicinal puposes by five ethnic groups in Papua. Utilizations of mangrove as traditional medicines could be used for treatments for twelve diseases or health syndromes, ranging from mosquito repellency, scabies medicine, cleanse for pregnancey, children’s speaking ability, insecticides, malaria medicine, tooth medicine, diarrhoea, energy booster and stimulant for birth delivery. More importanly, the method of extraction, preparation and dosages of comsumption among five ethnics groups are almost similar.Keywords: Mangrove vegetation, traditional medicines, five ethnics, PapuaAbstrakVegetasi mangrove berperan penting dan cukup nyata, serta merupakan salah satu bagian penting dalam kehidupan masyarakat Papua, khususnya yang berdomisili di pesisir pantai. Mangrove dimanfaatkan sebagai sumber makanan, kayu bakar, obat-obatan tradisional, dan pelindung dari bahaya tsunami, badai, dan aberasi air laut. Penelitian ini dilakukan menggunakan metode observasi lapangan dan studi pustaka. Tujuan penelitian ini mengetahui pemanfaatan vegetasi mangrove sebagai tumbuhan berkhasiat obat pada lima suku pesisir di tanah Papua. Hasil penelitian menunjukkan bahwa sebanyak tujuh jenis dari lima famili vegetasi mangrove yang dimanfaatkan sebagai tumbuhan berkhasiat obat, untuk mengobati dua belas penyakit atau gejala penyakit, termasuk pestisida alami.Kata kunci: Vegetasi mangrove, obat tradisional, lima suku, Papua